Do you have feet in your shoes? Innovation and resilience in a footwear industrial district in Brazil - Luiz Fernando Câmara Viana; Valmir Emil Hoffmann; Hugo Pinto; Isabel Diez Vial (Investigaciones Regionales - Journal of Regional Research)
is study examines innovation as a shock reaction in the process of regional economic resilience, focusing on a footwear industrial district in southern Brazil during the COVID-19 pandemic. e results show that innovation, a mechanism of adaptability, emerged in the industrial district not only to support economic recovery, but also to mitigate the adverse eﬀects. Firms implemented novel marketing and sales processes, and some also had to change their information and communication systems or organisational structure to support e-commerce. As such, this study highlights the inﬂuence of adaptability on economic resistance.